Strategi Dakwah Melalui Mentoring Dalam Meningkatkan Pemahaman Keagamaan Di Kursus Kader Dakwah MAN 2 Model Medan - Elvira Nurlita Sibarani; Waizul Qarni (STAI Bumi Silampari, 2026)
This study aims to analyze the mentoring-based da'wah strategy implemented in the Kursus Kader Dakwah (KKD) program at MAN 2 Model Medan, identify its supporting and inhibiting factors, and evaluate its effectiveness in improving cadres’ religious understanding. The research employs a qualitative field research approach. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the mentoring-based da'wah strategy is systematically managed through the application of POAC management functions (planning, organizing, actuating, and controlling). Planning is conducted through structured material preparation and scheduling, organizing through clear task distribution, actuating through interactive and dialogical learning processes, and controlling through continuous evaluation and supervision. The strategy has proven effective in enhancing cadres’ religious understanding, as indicated by increased Islamic knowledge, improved Qur’anic reading skills, and the development of religious attitudes and spiritual awareness. Although challenges such as limited time and participant fatigue were encountered, they were addressed through flexible implementation and institutional support. Overall, systematically managed mentoring serves as an effective strategy for strengthening religious understanding within the madrasah environment.